ANALISIS PENYEBAB KEJADIAN LUAR BIASA (KLB) KERACUNAN MAKANAN (Studi Kasus di PT BK di Kabupaten Bogor) - Sudikno -; Suhartini - (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2006)
Background: Food poisoning may cause severe damage to the health of human being and even death. There were 90 cases of food poisoning outbreak between 1997 and 1999 in West Java involving 508 victims and 90 deaths. In order to prevent the outbreak, it is important to find the cause and mechanism of poisoning caused by food. Objective: To find the cause and the mechanism of food poisoning outbreak in PT BK in Bogar District, 25-26 February, 2005. Methods: Data used in this study are the information gained from the investigation report of Food Poisoning Outbreak at PT BK on 25-26 February 2005 11 Bogar District. The investigation involved 307 workers who consumed food in company's canteen. Results: It was found that raw meat was coot21ninated with E.coli and lactobacillus. E. coli was also found in beefsteak served on 25 February 2005. The logistic regression test found that the workers who consumed beefsteak have 10.25 times to get poisoned than those who did not consume beefsteak. Conclusion: Beefsteak which contaminated with E. coli may caused food poisoning outbreak in PT BK. [Penel Gizi Makan 2006, 29(2): 85-91]